The quest for Factor VIIa exosite inhibitors. (22nd May 2007) - Amour, A.; Hutchinson, J.; Ruiz Avendaño, A.M.; Ratcliffe, S.; Alvarez, E.; Martin, J.; Toomey, J.R.; Senger, S.; Wolfendale, M.; Mooney, C.
Abstract : Coagulation proteases are involved in a highly orchestrated proteolytic cascade which is essential for haemostasis and blood clotting. In particular, the initiator of the coagulation cascade, Factor VIIa, binds to its cofactor, tissue factor, and its substrate, Factor X, via exosite interactions to form a ternary catalytic complex named extrinsic Xase. These exosite interactions have also been shown to allosterically induce the active conformation of the catalytic site of Factor VIIa. We have developed a direct continuous fluorescence polarization-based extrinsic Xase assay, which has been used to screen in excess of 1 million structurally diverse low-molecular-mass compounds as a potential starting point for the development of anticoagulants. The primary screen hits were categorized with deconvolution assays into either active-site or exosite inhibitors. The latter category of hits displayed both competitive and uncompetitive modalities of inhibition with respect to Factor X activation. An uncompetitive mechanism of action is of particular interest as it offers a hypothetical inhibitory advantage in the context of inhibiting a proteolytic cascade such as the blood coagulation pathway.